KURIKULUM DAN METODOLOGI PEMBELAJARAN PESANTREN - Anas, A Idhoh (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2012)
Abstract: Education is possibly to have people attain the perfection of life both in their relationship with God, fellow human beings and nature. A well relationship is only possible if people have a balance between their orientation in the world and in the hereafter. Therefore, in order to achieve the aforementioned objective, they should have adequate religious education and general equally through educational institutions. One of the Islamic educational institutions is a dormitory or boarding school where students (Islamic pupils) learn to improve the Islamic religion. Education on Islamic educational institutions also aims to establish a generation of believers-Muslim virtuous, health, broad-minded, and social, rise intelligent scholars who have equal devotions and thought, as well as establish nationalism of Indonesian citizen who have a faithful and pious to Allah Almighty. In general, Islamic educational institutions are classified into three categories: a) traditional pesantren (Salaf), which still retains the traditional teaching methods and teaching materials with classic books (yellow book), b) modern pesantren (khalaf), which seeks to fully integrate the classical and the current school and university system, and 3) semi salaf and khalaf Islamic schools who defend the teaching of classical Islamic books, as well as open public educational institutions (formal or non-formal education).